Implementation of the Flipped Classroom Learning Model to Improve Students' Self-Regulated Learning - Wijayanto, Zainnur; Mutiara, Hikmah; Pardimin, Pardimin (FKIP Universitas Lampung, 2022)
This study aims to determine the effectiveness of the Flipped Classroom learning model in terms of self-regulated learning on student learning outcomes. This study used a quasi experimental design in SMP Muhammadiyah 1 Gamping with the subject of the study being the experimental group totaling 32 students and the control group totaling 32 students. Based on the result of data analysis shows that the application of the Flipped Classroom learning model is more effective than application of the direct learning model and has a significant interaction between the learning model and the self-regulated learning. This can be strengthened by the result of interactions with the learning model and the self-regulated learning of Sig=0,044<0,05 so that the learning model affects the self-regulated learning of students. The Flipped Classroom learning model can be used in mathematics as an alternative learning model, especially in flat face three dimensional objects. Keywords: effectiveness, flipped classroom learning model, self-regulated learning, learning outcomes DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1123-1134